3-Pyrrolyl-oxindoles as efficient nucleophiles for organocatalytic asymmetric synthesis of structurally diverse 3, 3′-disubstituted oxindole derivatives. Issue 4 (25th November 2014) - Cui, Bao-Dong; You, Yong; Zhao, Jian-Qiang; Zuo, Jian; Wu, Zhi-Jun; Xu, Xiao-Ying; Zhang, Xiao-Mei; Yuan, Wei-Cheng
Abstract : An organocatalytic asymmetric reaction of 3-pyrrolyl-oxindoles to nitroalkenes was developed to afford a range of 3-pyrrolyl-3, 3′-disubstituted oxindoles in excellent yields. Abstract : A range of 3-pyrrolyl-3, 3′-disubstituted oxindoles were smoothly obtained via the reaction of 3-pyrrolyl-oxindoles with nitroalkenes using an organocatalyst. The usefulness of the protocol was also demonstrated by the versatile conversions of the Michael adducts into other functionalized 3, 3′-disubstituted oxindoles, as well as into the analogues of some valuable natural products.